2021
DOI: 10.1124/molpharm.120.000168
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure to SCO-267, an Allosteric GPR40 Full Agonist, Is Effective in Improving Glycemic Control in Rats

Abstract: Full agonist-mediated activation of free fatty acid receptor 1 (FFAR1/GPR40) alleviates diabetes in rodents. Considering that diabetes is a chronic disease, assessment of treatment durability of chronic exposure to a GPR40 full agonist is pivotal for treating patients with diabetes. However, the physiological significance of chronic in vitro and in vivo exposure to GPR40 full agonists is largely unclear. Here, we evaluated the in vitro and in vivo effects of chronic treatment with SCO-267, a GPR40 full agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, multiple doses of SCO-267 were able to repeatedly simulate the secretion of insulin, glucagon, GLP-1, GIP, and PYY. A preclinical study demonstrated that chronic 24-h exposure to SCO-267 for 5 weeks was highly effective in improving glucose tolerance in diabetic rats (19). Overall, these results suggest that repeated once-daily oral administration of SCO-267 is likely to improve glycemic control in patients with diabetes, and its use should be evaluated for longer periods in clinical trials.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, multiple doses of SCO-267 were able to repeatedly simulate the secretion of insulin, glucagon, GLP-1, GIP, and PYY. A preclinical study demonstrated that chronic 24-h exposure to SCO-267 for 5 weeks was highly effective in improving glucose tolerance in diabetic rats (19). Overall, these results suggest that repeated once-daily oral administration of SCO-267 is likely to improve glycemic control in patients with diabetes, and its use should be evaluated for longer periods in clinical trials.…”
Section: Discussionmentioning
confidence: 83%
“…SCO-267 at a dose of 0.3 mg/kg exhibited a C max value of 22.7 ng/mL and was more effective at improving glucose control than the clinically translatable doses of sitagliptin, a dipeptidyl peptidase 4 inhibitor, and fasiglifam in diabetic rats (16,17). In addition, a preclinical study demonstrated that chronic 24-h exposure to SCO-267 was highly effective in improving glycemic control in diabetic rats (19). Therefore, oncedaily dosing of $10 mg SCO-267 might be sufficient to improve glycemic control for 24 h in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…SCO‐267 can decrease liver triglyceride content and plasma alanine aminotransferase amount without affecting food intake and body weight in NAFLD mouse (Ookawara et al, 2020). It has been demonstrated that SCO‐267 improved glucose tolerance in rats after 15 days of dosing and chronic exposure to SCO‐267 increased pancreatic insulin levels (Koyama et al, 2021). Clinical experiments indicated that SCO‐267 was safe and well tolerated (Nishizaki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%